Aberrant Activation of the Intrarenal Renin-Angiotensin System in the Developing Kidneys of Type 2 Diabetic Rats - Fan, Y.-Y.; Kobori, H.; Nakano, D.; Hitomi, H.; Mori, H.; Masaki, T.; Sun, Y.-X.; Zhi, N.; Zhang, L.; Huang, W.; Zhu, B.; Li, P.; Nishiyama, A. (Hormone and Metabolic Research, 2013)
We have previously reported that intrarenal angiotensin II (Ang II) levels are increased long before diabetes becomes apparent in obese Otsuka-Long-Evans-Tokushima-Fatty (OLETF) rats, a model of type 2 diabetes. In this study, we examined the changes in intrarenal renin-angiotensin system (RAS) activity in the developing kidneys of OLETF rats. Ang II contents and mRNA levels of RAS components were measured in male OLETF and control Long-Evans Tokushima (LETO) rats at postnatal days (PND) 1, 5, and 15, and at 4–30 weeks of age. In both LETO and OLETF rats, kidney Ang II levels peaked at PND 1, then decreased during the pre- and post-weaning periods. However, Ang II levels and gene expression of RAS components, including angiotensinogen (AGT), renin, and angiotensin-converting enzyme (ACE), were not significantly different between LETO and OLETF rats. Intrarenal Ang IIcontents further decreased during puberty (from 7 to 11 weeks of age) in LETO rats, bur not in OLETF rats. At 11 weeks of age, kidney Ang II levels, urinary AGT excretion, and mRNA levels of AGT and renin were higher in OLETF rats than in LETO rats, while blood glucose levels were not significantly different between these groups of rats. These data indicate that continued intrarenal expression of Ang II during pubescence contributes to the increases in intrarenal Ang II levels in prediabetic OLETF rats, and is associated with increased intrarenal AGT and renin expression. Inappropriate activation of the intrarenal RAS in the prediabetic stage may facilitate the onset and development of diabetic nephropathy in later life.
Keywords: angiotensin II; developing kidney; diabetes; angiotensinogen